Formulation of an environmental resilience index as an indicator of sustainability in Selangor - Asmawi, M. Zainora; Syed Zainal Yussof, Sharifah Husna; Ibrahim, Illyani; Wan Mohd Rani, Wan Nurul Mardhiah (2021)
It is evident that global climate change has significantly affected the local environmental context in many towns. The abundance of environmental resources in Malaysia provides many environmental services towards the nation's development. However, disasters such as flooding, landslides and earthquakes stress the importance of environmental sensitive areas (ESAs) as natural defence agents for a resilient and sustainable town. Thus, the presence of a framework to measure the level of resilience for an area is crucial. However, there is no detailed model explicitly dedicated to environmental resilience in the Malaysian context. This research aims to develop a methodological framework to measure the environmental resilience index (ERI) in Selangor, Malaysia, which stakeholders could use, especially the Local Planning Authority (LPA). The state of Selangor is chosen as a study area, taking into consideration its rapid economic growth and the availability of its enormous natural resources. The objectives are to identify critical factors of environmental resilience, generate the ERI results to understand the spatial distribution pattern and produce a model of environmental resilience index in the Geographical Information System (GIS) database system. The research undertook comprehensive document analysis and systematic literature review in developing the ERI. This data used to analyse are majorly secondary data from official reports of responsible technical departments and agencies in Malaysia to ensure validity and reliability of data. The research developed a framework of ERI, consisting of five environmental components: environmental resources, built environment, climate condition, natural disasters, and environmental issues with 40 indicators. The output of this analysis was generated using ArcGIS software related to the weightage of different components and sub-components. The results show that all the districts in Selangor have an ERI level of moderate level, reflecting the resilience status should there be any disaster.